A comprehensive experimental emulation for OTFS waveform RF-Impairments - Abushattal, Abdelrahman; Zegrar, Salah Eddine; Yazgan, Ayhan; Arslan, Hüseyin (MDPI, 2023)
The orthogonal time-frequency space (OTFS) waveform exceeds the challenges that face orthogonal frequency division multiplexing (OFDM) in a high-mobility environment with high time-frequency dispersive channels. Since radio frequency (RF) impairments have a direct impact on waveform behavior, this paper investigates the experimental implementation of RF-impairments that affect OTFS waveform performance and compares them to the OFDM waveform as a benchmark. Firstly, the doubly-dispersive channel effect is analyzed, and then an experimental framework is established for investigating the impact of RF-impairments, including non-linearity, carrier frequency offset (CFO), I/Q imbalances, DC-offset, and phase noise are considered. The experiments were conducted in a real indoor wireless environment using software-defined radio (SDR) at carrier frequencies of (Formula presented.) GHz and 5 GHz based on the Keysight EXG X-Series devices. The comparison of the performances of OFDM and OTFS in the presence of RF-impairments reveals that OTFS significantly outperforms OFDM.
Keywords: OTFS; OFDM; RF-Impairments; I/Q Imbalances; DC-Offset; Phase Noise; Carrier Frequency Offset